Computer network with heterogeneous input stream of requests from the relative priorities - Пустовойтов, Павел Евгеньевич (Eastern-European Journal of Enterprise Technologies, 2011)
The model of network hub was developed using queuing theory with uniform stream with relative priority. It was calculated the probabilities of system states